2017
DOI: 10.3171/2016.7.peds16310
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of vestibulo-ocular dysfunction in pediatric sports-related concussion

Abstract: OBJECTIVE There were 2 objectives of this study. The first objective was to identify clinical variables associated with vestibulo-ocular dysfunction (VOD) detected at initial consultation among pediatric patients with acute sports-related concussion (SRC) and postconcussion syndrome (PCS). The second objective was to reexamine the prevalence of VOD in this clinical cohort and evaluate the effect of VOD on length of recovery and the development of PCS. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 40 publications
(45 reference statements)
4
48
1
Order By: Relevance
“…Motion sickness arises when there is a neural mismatch between an internal model of how a dynamic environment should respond and the actual behavior of the environment [34]. The neural mismatch leading to motion sickness and subsequent nausea may be amplified post injury due to vestibular dysfunction associated with concussion [25]. This mismatch may be further exacerbated in a cohort with pre-existing vestibular deficits, which may explain the higher incidence of post-concussive nausea that we observed in the pre-injury anxiety group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motion sickness arises when there is a neural mismatch between an internal model of how a dynamic environment should respond and the actual behavior of the environment [34]. The neural mismatch leading to motion sickness and subsequent nausea may be amplified post injury due to vestibular dysfunction associated with concussion [25]. This mismatch may be further exacerbated in a cohort with pre-existing vestibular deficits, which may explain the higher incidence of post-concussive nausea that we observed in the pre-injury anxiety group.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that anxiety disorders cause the vestibular system to rely more heavily on visual inputs for balance than those without anxiety -leading to Vestibular-Ocular Dysfunction (VOD) [22]. VOD following concussion has been independently associated with a 4x greater risk of prolonged recovery [25]. Therefore, pre-existing VOD may be associated with pre-injury anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This is of concern due to reports that as many as 50% of those with sports-related concussion have vestibular-ocular dysfunction, which is predictive of prolonged recovery. 17,64 Alsalaheen and colleagues 7 completed a retrospective study examining the efficacy of VR for individuals with concussion. Of the 114 patients, 67 (59%) were children (median age: 16 years, range: 8-18 years).…”
Section: Efficacy Of Vestibular Rehabilitation For Childrenmentioning
confidence: 99%
“…Previous research has shown that demographic and injury characteristics such as adolescent age [4,[9][10][11], female sex [9,10,[12][13][14], history of prior concussion [15,16], and amnesia [5,12,17] are associated with prolonged recovery from concussion. Additional research shows that symptom burden, defined by a patient's total symptom score (TSS), is the most consistent predictor of prolonged recovery among concussed youth [5,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%